Key Components of Sarva Shiksha Abhiyan in India: Universalizing Elementary Education in India (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Sarva Shiksha Abhiyan (SSA) is an effort to universalize elementary education through community-ownership of the school system. It is a response to the demand for quality basic education all over the country. It is an attempt to provide an opportunity for improving human capabilities of all children, through provision of community-owned quality education in a mission mode. It forms the cornerstone of government interventions in the sphere of elementary education for all children. It was launched in November 2000 as an umbrella programme to support and build on primary and elementary education projects. The programme aims to ensure five years of primary education for all children in the age group of 6-14 years by 2007 and eight years of schooling by 2010.